2019
DOI: 10.1121/1.5139423
|View full text |Cite
|
Sign up to set email alerts
|

Individual predictors of response to biofeedback training for second-language production

Abstract: While recent research suggests that visual biofeedback can facilitate speech production training in clinical populations and second language (L2) learners, individual learners' responsiveness to biofeedback is highly variable. This study investigated the hypothesis that the type of biofeedback provided, visual-acoustic versus ultrasound, could interact with individuals' acuity in auditory and somatosensory domains. Specifically, it was hypothesized that learners with lower acuity in a sensory domain would show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 78 publications
1
25
1
Order By: Relevance
“…There was no relationship between individual accuracy in speech sound perception and production, in novice learners, suggesting the absence of a link between the two domains, at least when learning "novel" perceptually-similar L2 sounds distinct from native categories. This result is consistent with previous research, showing that, while experienced L2 speakers show a moderate-to-strong relationship between L2 perception and production (Baker & Tro movich, 2006;Bettoni-Techio et al, 2007;Flege, 1993Flege, , 1999Flege et al, 1997Flege et al, , 1999Flege & Eefting, 1987a;Flege & Schmidt, 1995;Hattori & Iverson, 2010;Jia et al, 2006;Kluge et al, 2007;Zhang & Peng, 2017), speakers with less experience or novice learners show only weak or no relationship at all (Jia et al, 2006;Kartushina et al, 2015;Kartushina & Frauenfelder, 2014;Li et al, 2019). This may indicate that the two domains align with experience (Flege and Schmidt, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…There was no relationship between individual accuracy in speech sound perception and production, in novice learners, suggesting the absence of a link between the two domains, at least when learning "novel" perceptually-similar L2 sounds distinct from native categories. This result is consistent with previous research, showing that, while experienced L2 speakers show a moderate-to-strong relationship between L2 perception and production (Baker & Tro movich, 2006;Bettoni-Techio et al, 2007;Flege, 1993Flege, , 1999Flege et al, 1997Flege et al, , 1999Flege & Eefting, 1987a;Flege & Schmidt, 1995;Hattori & Iverson, 2010;Jia et al, 2006;Kluge et al, 2007;Zhang & Peng, 2017), speakers with less experience or novice learners show only weak or no relationship at all (Jia et al, 2006;Kartushina et al, 2015;Kartushina & Frauenfelder, 2014;Li et al, 2019). This may indicate that the two domains align with experience (Flege and Schmidt, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…To examine each participant's overall production variability across repeated utterances of the two vowels, the midpoint F1 and F2 values of each token were used to compute an area of the ellipse measure for each vowel. Following Li et al (2019), trial-to-trial production variability was quantified as the area of an ellipse representing the 95% confidence interval around the multivariate mean of the distribution of F1 and F2 values. Area of the ellipse was calculated first for each vowel separately.…”
Section: Area Of the Ellipsementioning
confidence: 99%
“…For example, multidirectional changes in the relative EEG intensity in the brain hemispheres can cause enhancement of cognitive activity and attention processes (Putman, 2005), as well as improvement of executive functions (Kim et al, 2013;Landes et al, 2017). Studies have shown that the effectiveness of biofeedback is determined by many factors such as: motivation (Kleinman, 1981;Saho & Harano, 1984), training (Keefe & Gardner, 1979), respiration (Conde Pastor et al, 2008), and some individual characteristics (Suter, 1979;Li et al, 2019). In general, by unlocking the body's full potential and mobilizing resources to achieve the goal, one can eliminate excessive psycho-emotional tension and improve the efficiency and rationality of activities not only during biofeedback trainings, but also thereafter.…”
Section: Biofeedbackmentioning
confidence: 99%